2014
DOI: 10.1007/s00268-014-2765-y
|View full text |Cite
|
Sign up to set email alerts
|

Sutured Repair of Primary Small Umbilical and Epigastric Hernias: Concomitant Rectus Diastasis Is a Significant Risk Factor for Recurrence

Abstract: We strongly recommend preoperatively checking for rectus diastasis and using nonabsorbable sutures as an alternative to mesh repair only when repairing small umbilical or epigastric hernias (<2 cm) and there is no concomitant rectus diastasis. Patients with coexistent rectus diastasis definitely benefit from mesh-based repair of the midline to decrease the recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 22 publications
4
62
0
15
Order By: Relevance
“…The presence of a rectus diastasis and a concomitant umbilical or epigastric hernia presents a significant challenge with respect to operative management. The recurrence rate after small umbilical or epigastric hernia repair with a concomitant rectus diastasis has been reported to be higher than that in patients without a rectus diastasis. The literature is limited.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a rectus diastasis and a concomitant umbilical or epigastric hernia presents a significant challenge with respect to operative management. The recurrence rate after small umbilical or epigastric hernia repair with a concomitant rectus diastasis has been reported to be higher than that in patients without a rectus diastasis. The literature is limited.…”
Section: Resultsmentioning
confidence: 99%
“…(5) No existe consenso en relación a las indicaciones ni al tipo de tratamiento quirùrgico sugerido ,pero si la DR es sintomática o asociada con hernias de línea media (umbilical y/o epigástrica), la cirugía concomitante sería la opción más válida.…”
Section: Drunclassified
“…Patients with RAD typically are middle-aged and older men with central obesity, or small, fit women who have carried a large fetus or twins to term [1]. Rectus abdominis diastasis is often seen in umbilical and/or epigastric hernia (45%) [2]. Patients with small umbilical and/or epigastric hernia with concomitant RAD, who underwent suture repair, had a significantly higher recurrence rate (31.2% vs. 8.3%; p  < 0.001) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rectus abdominis diastasis is often seen in umbilical and/or epigastric hernia (45%) [2]. Patients with small umbilical and/or epigastric hernia with concomitant RAD, who underwent suture repair, had a significantly higher recurrence rate (31.2% vs. 8.3%; p  < 0.001) [2]. The authors concluded that umbilical and/or epigastric hernias, regardless of size, with concomitant RAD require mesh repair owing to unacceptably higher recurrence rates [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation